Computational Science and High Performance Computing III - E. H. Hirschel, W. Schröder, K. Fujii, W. Haase, B. Leer, M. A. Leschziner, M. Pandolfi, J. Periaux, A. Rizzi, B. Roux, Yu. Shokin, Egon Krause, Yurii I. Shokin, Michael Resch, Nina Shokina. (Springer, 2017)
271p.